2017
DOI: 10.2147/ndt.s150488
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory improvement in first-episode psychosis <em>APOE-</em>&epsilon;4 carriers: a pleiotropic effect?

Abstract: BackgroundVerbal memory impairment is a core feature in schizophrenia even at early stages of the disease, but its etiopathogenesis is not fully understood. The APOE-ε4 is the main genetic risk factor for late-onset Alzheimer’s disease. Our primary goal was to ascertain whether APOE-ε4 status had a pleiotropic effect in early stages of the illness.Participants and methodsA total of 86 first-episode psychosis (FEP) outpatients and 39 healthy volunteers were recruited. Demographic and clinical data, APOE genotyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…In addition, a study found that schizophrenia patients with ApoEε4 carriers had significantly lower verbal memory score assessed by the Brief Assessment of Cognition in Schizophrenia (BACS) [22]. Another study showed an interaction between the ApoE ε4 allele, first-episode psychosis (FEP), and the improvement in verbal memory over time measured by California Verbal Learning Test (CVLT) [94]. These inconsistent findings of cognitive deficits in patients with schizophrenia may be partly due to the combined effects of different cognitive measurement tools and ApoE genotypes.…”
Section: Genotype Effects On Serum Apob Level and Cognition In Patientsmentioning
confidence: 99%
“…In addition, a study found that schizophrenia patients with ApoEε4 carriers had significantly lower verbal memory score assessed by the Brief Assessment of Cognition in Schizophrenia (BACS) [22]. Another study showed an interaction between the ApoE ε4 allele, first-episode psychosis (FEP), and the improvement in verbal memory over time measured by California Verbal Learning Test (CVLT) [94]. These inconsistent findings of cognitive deficits in patients with schizophrenia may be partly due to the combined effects of different cognitive measurement tools and ApoE genotypes.…”
Section: Genotype Effects On Serum Apob Level and Cognition In Patientsmentioning
confidence: 99%
“…Among the APOE polymorphism-associated traits that appear to have AP characteristics are included the different biochemical consequences that ApoE2, ApoE3, ApoE4 proteins have on the metabolism of cholesterol, which have important implications, among others, on the metabolism of β-amyloid and synaptogenesis resistance in younger vs. aged mammalians, and could so explain the “paradoxical” beneficial effects of APOE 4 on specific cognitive skills (e.g. verbal memory in schizophrenic patients [78], memory performance [79], and attention in young [80]), and the observation that APOE 4 is an advantageous factor on survival and infertility in infectious environments [81,82], or that APOE alleles are associated with conscientiousness personality-trait in relationship to gray matter volume [7] and greater cortical connectivity [83]. Figure 1 shows graphs describing the antagonistic pleiotropy concept applied to APOE polymorphism.…”
Section: Apoe and Antagonistic Pleiotropymentioning
confidence: 99%
“…82 Thirteen studies obtained nonsignificant results. 59,60,[62][63][64]66,[70][71][72]76,81,83,84 Genome-wide association studies…”
Section: Other Candidate Genesmentioning
confidence: 99%